Measuring Satisfaction in Breast Cancer Patients Receiving Ambulatory Care: A Validation Study - Wadasadawala, Tabassum; Mangaj, Akshay; Mokal, Smruti; Pathak, Rima; Sarin, Rajiv; Gaikar, Mithila; Nair, Nita; Bajpai, Jyoti; Joshi, Shalaka; Gulia, Seema (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Patient satisfaction constitutes a vital service quality indicator. It provides a measure of the gap in health-care requirements and patients' expectations.Objective The aim of this study was to perform linguistic validation of the questionnaire assessing satisfaction with outpatient care.Materials and Methods A tool for measuring patient satisfaction was developed and validated at our institute in the English language. This tool was translated into Hindi and Marathi. Subsequently, 339 patients diagnosed with breast cancer consulting in the outpatient department from the different parts of India and having diverse linguistic and socioeconomic backgrounds were enrolled. Patients were asked to complete the satisfaction tool after consultation at a single point of time in a prospective manner.Results All patients completed the questionnaire. The questionnaire was filled by 120, 116, and 103 patients in Hindi, Marathi, and English, respectively. Both convergent validity and discriminant validity were supported as the correlation coefficient was >0.4 for all items within a scale and <0.7 between different scales. Factor analysis was valid for all except for open-end questions. The internal consistency was >0.9 for all the questions. The mean overall satisfaction score was 88.35 (standard deviation: 19.63). Patients were satisfied in all the aspects of the consultation process, including appointment scheduling, assistant medical staff and faculty, and treating physician. However, some expressed dissatisfaction toward long-waiting times.Conclusion The translated tool is reliable and valid and effectively measures the satisfaction of patients receiving ambulatory care.
Keywords: breast cancer; outpatient; patient satisfaction; satisfaction survey